Efficacy of the Endolysin-Based Antibacterial Gel for Treatment of Anaerobic Infection Caused by Fusobacterium necrophorum - Daria V. Vasina; Nataliia P. Antonova; Aleksei M. Vorobev; Aleksei I. Laishevtsev; Andrei V. Kapustin; Eldar R. Zulkarneev; Svetlana S. Bochkareva; Irina A. Kiseleva; Mariia N. Anurova; Andrei V. Aleshkin; Artem P. Tkachuk; Vladimir A. Gushchin (MDPI AG, 2021)
Abscess formation is a common complication of severe life-threatening infections caused by obligate anaerobes. Fusobacterium necrophorum is among the frequently detected anaerobic pathogens from clinical specimens associated with liver abscesses, skin and soft tissue infections, or oral abscesses. The antimicrobial therapy for this kind of infection needs to be optimized. Here, we examined the possibility of treating F. necrophorum-induced abscess wound infections with candidate therapeutics based on three endolysins with activity against a broad spectrum of aerobe Gram-negative pathogens. Antibacterial gel containing three Gram-negative bacteria-targeting endolysins, LysAm24, LysAp22, and LysECD7, was formulated for topical use. Abscess formation was induced in rabbits with F. necrophorum and caused systemic infection. The survival and lifespan of the animals, general parameters, and biochemical and hematological blood tests were analyzed to assess the effectiveness of the gel treatment for the wound infection. The administration of the investigated gel twice per day for 5 days resulted in less acute inflammation, with decreased leukocytes and segmented neutrophils in the blood, retardation of infection progression, and an almost two-fold increase in the lifespan of the animals compared to the placebo group. The results indicate that endolysin-based therapy is an effective approach to treat anaerobic bacterial infections. The use of endolysins as independent pharmaceuticals, or their combination with antibiotics, could significantly reduce the development of complications in infectious diseases caused by sensitive bacterial species.